Leveraging Social Media Marketing in Healthcare-Based Non-profit Organisations: Insights from the Technology Acceptance Model - Shaun Thomas; Rodney Duffett (Information Management and Technology: The Proceedings of the 10\(^th\) International Conference on Business and Management Dynamics (ICBMD), Edition 1, 2025)
This study seeks to identify the variables that both positively and negatively influence the usage of social media marketing (SMM) by South African healthcare-based non-profit organisations (HB NPOs) based on the Technology Acceptance Model (TAM). Social media has emerged as a key tool for fostering dialogue between HB NPOs and their stakeholders in South Africa. A majority of NPOs agree that marketing is essential for raising funds and awareness, yet comparatively few partake extensively in new digital marketing activities. Based on the researcher’s expertise (judgemental sampling), the study selected thirteen respondents (marketing and/or social media managers, coordinators, and directors) to participate. The study used a qualitative approach through semi-structured interviews to understand the perspectives of HB NPOs and their use of social media marketing (SMM). The interviews were transcribed and analysed using ATLAS.ti. The study elucidates motivational variables influencing the actual usage of SMM via the integration of the TAM and considers aspects like external variables, perceived usefulness, perceived ease of use, and behavioural intention within an HB NPO context. The research affirms the importance of the use of SMM for the sustainability and promotion of HB NPOs (increased awareness, donation appeals, community relationships, cost-effective platform to raise funds, powerful images and patient stories lead to brand emotions and positive image), but also reveals a number of negative influences that impede the usage of SMM by HB NPOs (lack of government support, corporate sponsors, time, understanding, capacity, resources, and a small donor pool). Practically, SMM presents an opportunity for HB NPOs to allocate necessary resources toward its strategic use as a communication approach, enabling them to take advantage of the beneficial and sustainable influences. Theoretically, this investigation supports the foundational principles of the TAM and adds to it from a qualitative perspective by highlighting the sustainable and negative influences of external factors, perceived usefulness and ease of use, and behavioural intentions based on SMM usage by HB NPOs. The study enhances understanding of digital marketing, broad NPO management, and the organisational behaviour of HB NPOs in a developing nation context via the TAM framework.